Modelling and Simulation of Multi-vessel Batch Distillation Column - Nurul Hazwani, Sabri; Anwaruddin, Hisyam; Badhrulhisham, Abdul Aziz (AIDIC Servizi, 2017)
Market demand of specialty chemicals, biochemical and pharmaceuticals are increasing. Batch distillation is considered as the most suitable distillation operation to separate all those chemicals due to its flexibility, operability and lower capital cost. Multi-vessel batch distillation is an improvement of less energy efficient batch distillation. This paper focuses on modelling and simulation of multi vessel batch distillation column under total reflux operation for separating a ternary mixture. Total reflux operation leads to production of high purity product. In industry, the modelling and simulation play a very important role. It can help with the description of the system and the choice of the optimal control strategy. The main objective of this paper is to determine the mathematical model of multi-vessel batch distillation which usually precedes the design of the controller. Mathematical model is firstly developed based on the first principles and ordinary differential equations (ODE). MATLAB Simulink is employed to perform the simulation. The vessel holdup is set based on product purity. The model is expected to produce stable response with the changing inputs variables and produce high purity product. The control strategy is determined.